National Identity and Religious Diversity - Kenneth Harttgen; Matthias Opfinger (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2012)
We construct a simple index for national identity using information from the World Values Survey on peoples attitudes towards the nation. We then analyze the relationship between national identity and religious diversity. The results show that religious diversity is significantly and negatively related to national identity. We also find support for the previous finding that ethnic diversity does not seem to be related to national identity. Apparently, religious diversity and the feeling of heterogeneity that goes along with it prevents people from forming a common identity. Besides, our results indicate that there is a negative correlation between national identity and the level of income. The prevention of discrimination against minority groups follows as an important policy advice.
Keywords: J15; O1; Z12; 330; National Identity; Religious Diversity; Identity Formation